2020
DOI: 10.1155/2020/3972390
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products: Review for Their Effects of Anti-HBV

Abstract: Hepatitis B is a global infectious disease, seriously endangering human health. Currently, there are mainly interferons and nucleoside analogues treatment of hepatitis B in the clinic, which have certain therapeutic effects on hepatitis B, but their side effects and drug resistance are increasingly prominent. Therefore, it is urgently needed to discover and develop new anti-HBV drugs, especially natural products, which have novel, high efficiency, and low toxicity anti-HBV compounds with novel antiviral mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…At 50 µg/mL, the C. xanthorrhiza extract reduced HBV DNA levels by 30% [65]. The xanthone compound mangiferin (53), isolated from Swertia mussotii, also induced a significant reduction in HBV DNA replication, with IC 50 values ranging from 0.01 to 0.13 mM [66,67]. Cao et al reported that dihydroxy-3,5-dimethoxyxanthone (54) and norswertianolin (55) isolated from Swertia yunnanensis exhibit inhibitory effects against HBV DNA replication in HepG2.2.15 cells, and methylation or glycosylation of the hydroxyl group of the compounds might be responsible for this inhibitory effect [38,66].…”
Section: Xanthone Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…At 50 µg/mL, the C. xanthorrhiza extract reduced HBV DNA levels by 30% [65]. The xanthone compound mangiferin (53), isolated from Swertia mussotii, also induced a significant reduction in HBV DNA replication, with IC 50 values ranging from 0.01 to 0.13 mM [66,67]. Cao et al reported that dihydroxy-3,5-dimethoxyxanthone (54) and norswertianolin (55) isolated from Swertia yunnanensis exhibit inhibitory effects against HBV DNA replication in HepG2.2.15 cells, and methylation or glycosylation of the hydroxyl group of the compounds might be responsible for this inhibitory effect [38,66].…”
Section: Xanthone Compoundsmentioning
confidence: 99%
“…The xanthone compound mangiferin (53), isolated from Swertia mussotii, also induced a significant reduction in HBV DNA replication, with IC 50 values ranging from 0.01 to 0.13 mM [66,67]. Cao et al reported that dihydroxy-3,5-dimethoxyxanthone (54) and norswertianolin (55) isolated from Swertia yunnanensis exhibit inhibitory effects against HBV DNA replication in HepG2.2.15 cells, and methylation or glycosylation of the hydroxyl group of the compounds might be responsible for this inhibitory effect [38,66]. Another xanthone compound, 1,5,8-Trihydroxy-3-methoxyxanthone (56), isolated from Swertia delavayi, exhibited significant inhibitory activity against HBV DNA replication, with IC 50 values of 0.09 and 0.05 mM/L (SI of 10.89) [66,68].…”
Section: Xanthone Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…This HbeAg level is an indicator of predicting that the patient is whether infectious to others or not ( Grimm et al, 2011 ). Piperine, ursolic acid, oleanolic acid, and (+)-cycloolivil-4′-O-β-d-glucopyranoside have been testified to decrease the synthesis of HbsAg and HbeAg in many studies ( Zhou et al, 2015 ; Tshilanda et al, 2019 ; Liu et al, 2020 ). Quercetin has also been reported to decrease their synthesis by 60% ( Parvez et al, 2020 ).…”
Section: Mechanistic Insight Of Antiviral Activities Of the Plant Metabolites Derived From Medicinal Plantsmentioning
confidence: 99%
“…The extracts of G. veitchiorum showed obvious inhibitory effects on RSV both in vivo and in vitro [123]. Lots of compounds isolated from Gentianeae had significantly anti-HBV and anti-HIV activity [79,[124][125][126][127].…”
Section: Antiviral Effectsmentioning
confidence: 99%